Cyber Victimization and Depression among Adolescents with Autism Spectrum Disorder: The Buffering Effects of Parental Mediation and Social Support - Wright, Michelle F (Journal of child & adolescent trauma, 2018)
The purpose of the present study was to examine the buffering effect of parental mediation of technology use and social support from parents on the association between cyber victimization and depression, assessed over one year. Participants were 113 7th through 9th graders from the Midwestern United States (age ranged from 12 to 17 years old; 86% were male) who were diagnosed with autism spectrum disorder. They completed questionnaires on their perceptions of parental mediation of technology use, perceived social support from parents, and self-reported face-to-face and cyber victimization and depression at Wave 1. One year later, at Wave 2, they completed a questionnaire on their depression. Results indicated that the associations between cyber victimization and depression were more negative at higher levels of perceived parental technology mediation and social support, while these associations were more negative at lower levels of these variables, after controlling for face-to-face victimization and Wave 1 depression.
Keywords: Asperger syndrome; Cyberbullying; Cyber aggression; Pervasive developmental disorder; Autistic disorder